Implementasi Layanan Outreach Pusat Pembelajaran Keluarga Sebagai Upaya Perlindungan Anak - Lila Hidayati; Rosyidatuzzahro Anisykurlillah (Universitas Musamus, Merauke, Papua, 2024)
Surabaya City Government initiated the Puspaga program as an effort to protect children from violence. However, the number of recipients of Puspaga counseling services is not proportional to the number of violence in Surabaya. There are still many people who need but are not reached by Puspaga services. The Lontar Village Puspaga seeks to bring access to services closer to the community, one of which is through outreach services. The purpose of this study is to find out a clearer picture of the outreach services carried out by the Lontar Village Puspaga Facilitator. This research uses descriptive qualitative methodology, with interviews, documentation, and observation as the main methods of data collection. Data analysis techniques through the process of data reduction, data display, and conclusion drawing. The results showed that the implementation of the Lontar Village Puspaga outreach service was running optimally according to the theoretical parameters that had been set. The community makes a case complaint which is then followed up by the Puspaga Facilitator through outreach services to identify needs for providing assistance to clients. The implementation of Puspaga outreach services still needs to be improved, especially on communication and resource indicators, such as intensifying socialization carried out by all elements that are obliged to implement this program through posters, social media, or door to door, as well as providing infrastructure facilities such as computers and printers in each rw hall with good conditions to facilitate Puspaga Facilitators in providing optimal services to the community.